PENGARUH HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG (Studi pada Pengguna Smartphone Samsung di Kota Semarang) - Amalia, Evi; Nurseto, Sendhang (Jurnal Ilmu Administrasi Bisnis, 2019)
People’s mobility is increasing rapidly, especially in how to communicate each other. Everyone has a cellphone for work, school, business and so fort. Mobile phones today are increasingly sophisticated with the latest technology called smartphones. Competition between smartphone manufacturers is getting tougher. Mobile phones today are increasingly sophisticated with the latest technology called smartphones. Competition between smartphone manufacturers is getting tougher. One of the smartphone brands that becomes market leader in Indonesia is Samsung. Price and brand image are factors that influence consumer to purchase Samsung smartphones. This research aims to determine the effect of price and brand image on consumer's decisions to purchase Samsung smartphone. The type of research that used in this study is explanatory research. The sampling technique uses accidental sampling and purposive sampling techniques. Data collection using questionnaires and google form. The number of samples taken was 100 respondents, who were users of the Samsung smartphone in Semarang. The study used to determine the effect of prices and brand image on cunsomer purchasing decisions using statistics with system of IBM SPSS version 21.0. The results of the research showed the price variable and brand image influence consumer's decision to purchase Samsung smartphones. Correlation coefficients of price variables and brand image on purchasing decisions have a strong relationship. Price and brand image gave positive and significant influence on the purchase decision. The advice that can be given to improve consumer's purchasing decisions in this research is companies can pay attention to pricing in order to be able to compete with other products and improve the brand image of Samsung smartphones.